STRATEGI ORANG TUA ASUH DALAM MEMBERIKAN MOTIVASI KEPADA SISWA YANG MALAS BELAJAR DI PANTI ASUHAN YATIM PUTRI AISYIYAH II SURAKARTA: STRATEGI ORANG TUA ASUH DALAM MEMBERIKAN MOTIVASI KEPADA SISWA YANG MALAS BELAJAR DI PANTI ASUHAN YATIM PUTRI AISYIYAH II SURAKARTA - lisa eko ayun safitri; Hera Heru Sri Suryanti (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2021)
The research objectives are 1) to find out the strategies of foster parents in motivating students used who arre lazy to study 2) to find out what obstacles are experienced by foster parents in motivating students who are lazy to study, and 3) to find out the impact of giving motivation to students who are lazy to study. this research was carried out at the Aisyiyah II women’s orphanage, Surakarta. The research method used is a descriptive qualitative research. Two sources of data are primary data and secondary data. Primary data is the subject that is used is documentation, the identity of the orphanage children, and archives about the orphanage children which are obtained directly. Research data collection is using several techniques such as intervierws, observation, and documentation. The observation technique used is directly with the subject. Then it was followed by interview techniques with orphanage children and foster parents, and documentation. The data validity technique source triangulation, and technical triangulation. Data analysis methods are 1) data collection, 2) data reduction, 3) data presentation, and 4) conclution. Based on the data analysis, it was concluted that in the Aisyiyah II Surakarta orphanage there were 25 children, while there were 3 children who were lazy to study and were motivated by foster parents through giving attention, appreciation, refreshing, rewards, and praise. Though the provition of motivational strategies by foster parents, the orphanage children began to increase their learning motivation. The conclution of this study showed that giving motivation was succesful and increased children’s learning motivation. Keywords : Foster Parents Strategy, Motivating Childrern Who Are Lazy To Learn